Travel Time Models and Throughput Analysis of Dual Load Handling Automated Storage and Retrieval Systems in Double Deep Storage - Dörr, Katharina (Wissenschaftliche Berichte des Instituts für Fördertechnik und Logistiksysteme des Karlsruher Instituts für Technologie, 2018)
A general analytical travel time model for the quadruple command cycle in double deep storage systems with a dual capacity load handling device is formulated and validated by means of a simulation model. Various routing and sequencing strategies are composed. A simulation model is used to compare strategies for differnt AS/RS configurations and settings to assess them in consideration of real-world cases. For selected strategies, analytical formulations are derived.